Biological characteristics and metabolic phenotypes of different anastomosis groups of Rhizoctonia solani strains - Meili Sun; Hancheng Wang; Guo Ye; Songbai Zhang; Zhen Li; Liuti Cai; Feng Wang (BMC Microbiology, 2024)
Abstract Background Rhizoctonia solani is an important plant pathogen worldwide, and causes serious tobacco target spot in tobacco in the last five years. This research studied the biological characteristics of four different anastomosis groups strains (AG-3, AG-5, AG-6, AG-1-IB) of R. solani from tobacco. Using metabolic phenotype technology analyzed the metabolic phenotype differences of these strains. Results The results showed that the suitable temperature for mycelial growth of four anastomosis group strains were from 20 to 30oC, and for sclerotia formation were from 20 to 25oC. Under different lighting conditions, R. solani AG-6 strains produced the most sclerotium, followed by R. solani AG-3, R. solani AG-5 and R. solani AG-1-IB. All strains had strong oligotrophic survivability, and can grow on water agar medium without any nitrutions. They exhibited three types of sclerotia distribution form, including dispersed type (R. solani AG-5 and AG-6), peripheral type (R. solani AG-1-IB), and central type (R. solani AG-3). They all presented different pathogenicities in tobacco leaves, with the most virulent was noted by R. solani AG-6, followed by R. solani AG-5 and AG-1-IB, finally was R. solani AG-3. R. solani AG-1-IB strains firstly present symptom after inoculation. Metabolic fingerprints of four anastomosis groups were different to each other. R. solani AG-3, AG-6, AG-5 and AG-1-IB strains efficiently metabolized 88, 94, 71 and 92 carbon substrates, respectively. Nitrogen substrates of amino acids and peptides were the significant utilization patterns for R. solani AG-3. R. solani AG-3 and AG-6 showed a large range of adaptabilities and were still able to metabolize substrates in the presence of the osmolytes, including up to 8% sodium lactate. Four anastomosis groups all showed active metabolism in environments with pH values from 4 to 6 and exhibited decarboxylase activities. Conclusions The biological characteristics of different anastomosis group strains varies, and there were significant differences in the metabolic phenotype characteristics of different anastomosis group strains towards carbon source, nitrogen source, pH, and osmotic pressure.